Initial Site Characterization and Development of Procedures for the Assessment of Groundwater Quality of Unsewered Subdivisions Built Directly on top of Fractured Paleozoic Sandstone, Eau Claire County, WI - Hook, Glen; Hooper, Robert L.; Vitale, Sarah A. (My University, 2019)
Groundwater is the primary source for both public and private water supplies in much of the country. In the Midwest, the Paleozoic sandstone, bedrock-aquifers are an increasingly important source of drinking water (e.g. Madison, WI; Twin Cities metro; Eau Claire, WI) and recent studies in Wisconsin and Minnesota have shown that groundwater flow in the sandstones occurs primarily along fractures and bedding planes, which increases the potential for contamination of a well when compared to an isotropic porous media. This study examines groundwater flow and quality beneath a recently developed unsewered subdivision built directly on top of the Cambrian sandstones (Mt Simon Fm., and Eau Claire Fm.) in the Eau Claire area. Subsurface geology was reconstructed using data collected from well construction records (depth of different geologic units) and outcrop investigations within and near the subdivision. The stratigraphy, combined with measurements of fracture spacing and orientation, is used to help understand groundwater flow. This study outlines the procedure for testing for specific human wastewater indicators (caffeine, artificial sweeteners, pharmaceuticals, and household disinfectants) using high-performance liquid chromatography paired with mass spec (HPLC-MS) to determine the impact of septic systems on local groundwater quality for subdivisions built on sandstone bedrock.
Color poster with text, images, charts, photographs, maps, and graphs.
Keywords: Groundwater quality; Septic systems; Eau Claire County (Wis.); Posters